MOTIVASI PENDERITA HIPERTENSI DI DESA KOBO KECIL MEMANFAATKAN PELAYANAN KESEHATAN DI PUSKESMAS KOTABANGUN - Kanine, Esrom; Pobela, Nelpi (JURNAL KEPERAWATAN, 2018)
Abstrac: Background: Internal and external factors influence motivation to hypertension patiens using facilitation at the Puskesmas Kotabangun. The people at Kobo Kecil village including age 30-55 year old on the survey result showed generally complain dizzyness, nausea and insomnia. not having a health insurance card has an impact on the lack of motivation to visit health facilities to check their blood pressure. Distance with health facilities impact to hypertension patients consumption herbal drugs.Aims: Identify the motivation of hypertensive patients to using health services at Puskesmas Kotabangun. Methods: This research using the design of quantitative research. Seventeen samples were recruited using purposive sampling strategy, using cross sectional. Some including age 30-55 year old, more than six month suffering from hypertension. Data was analyzed using Chi Square, with p value < 0,05. Result : there was significant relationship between factors of visit, distance to Puskesmas, insurance ownership and socio economic with motivation (p value less than alpha value of 0.05). While the attitude of health workers is not related to the lower motivation of patients seeking treatment at the Puskesmas Kotabangun. Conclusion : This findings describes hypertension patients have lower motivation to use health services at the Puskesmas Kotabangun Keywords : Motivation, Hypertension Patients